Acute cold exposure improves glucose tolerance and induces beta-cell secretion response linked to lipid utilization in young male with obesity - Chamorro, Rodrigo; Bertozzi, Beatrice; Backhaus, Jenny; Iwen, Karl A.; Rademacher, Leonie; Meyhoefer, Svenja; Lehnert, Hendrik; Meyhöfer, Sebastian M; Wilms, Britta (Experimental and Clinical Endocrinology & Diabetes)
Aims: In lean humans, cold-activated brown adipose tissue (BAT) is associated with improved insulin sensitivity and lipid metabolism. Metabolic consequences of acute cold exposure in obesity are less well characterized. We studied the effects of acute cold-activated BAT on markers of metabolic health in men with obesity but no other chronic diseases and aimed to characterize potential underlying mechanisms linked to cold exposure. Material and Methods: Fourteen young (mean age [±SEM]: 26.4±0.8 years) males with obesity (BMI 31.9±0.5 kg/m2; range: 30.4-35.6 kg/m2) participated in a randomized cross-balanced within-subject study with two experimental conditions, i.e., i) cold exposure (CE), using a water-perfused suit at 16.0°C, shivering excluded for in total 5 hours; and ii) thermoneutrality (TN), using the same water-perfused suit at 25°C. Lipid metabolism and relevant hormones were measured. Glucose tolerance, β-cell secretion, and insulin sensitivity were assessed by Botnia clamp. Expression profiles of selected genes regulating lipolytic and β-oxidation pathways were determined from peripheral blood mononuclear cells. Results: Upon CE, plasma noradrenaline levels increased relative to TN. CE decreased fasting glucose and improved glucose tolerance in parallel with increased β-cell response. Moreover, CE led to increased plasma triglycerides as well as expression levels of selected genes involved in lipid metabolism. Conclusions: The observed metabolic changes and increased gene expression regulating lipid transport and disposal point towards a cold-induced insulin feedback signal required to sustain BAT thermogenesis demands. Our study reveals acute metabolic effects of thermogenically activated BAT and potential mediating mechanisms in young men with obesity.